2010
DOI: 10.1007/s10067-010-1650-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings of neuro-Behcet’s disease

Abstract: Neurological manifestations present in 5% to 30% of patients with Behçet's disease. We studied consecutive patients with relapsing--remitting or progressive neuro-Behcet's disease who referred from January 2002 to January 2009 to Nemazee Hospital, Shiraz, southern Iran. Sequential MRIs were performed during clinical relapses in patients with relapsing--remitting course or during relentless progression after first referral of patients with progressive course. We reviewed 55 MRIs of 17 patients (ten men and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 17 publications
1
22
0
2
Order By: Relevance
“…Facing upcoming patients with this constellation, neurologists and rheumatologists needed to conduct tests like magnetization transfer ratio; MR spectroscopy; MR tractography; CSF IL-6, TNF-alpha, and other inflammatory markers; anti-GM1 antibody; hexosaminidase level; and superoxide dismutase type 1 gene studies to shed light on the probable association of these two mysterious diseases. Knowing that both ALS [27] and progressive NBD [28] have no efficacious treatments re-necessitates the indication of these studies.…”
Section: Discussionmentioning
confidence: 98%
“…Facing upcoming patients with this constellation, neurologists and rheumatologists needed to conduct tests like magnetization transfer ratio; MR spectroscopy; MR tractography; CSF IL-6, TNF-alpha, and other inflammatory markers; anti-GM1 antibody; hexosaminidase level; and superoxide dismutase type 1 gene studies to shed light on the probable association of these two mysterious diseases. Knowing that both ALS [27] and progressive NBD [28] have no efficacious treatments re-necessitates the indication of these studies.…”
Section: Discussionmentioning
confidence: 98%
“…CNS involvement is one of the most severe manifestations of BD [14]. Sometimes it is difficult to differentiate from multiple sclerosis, stroke, intracranial hypertension, meningoencephalitis and myelitis.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, an inflammatory condition such as sarcoidosis, Wegener's disease, multiple sclerosis (Balo's type) or granulomatous pseudotumour may lead to similar lesions [8]. It has been suggested that histopathological examination may be done to rule out infectious or tumoural diseases and to avoid the inadequate use of immunosuppressive agents in previous reports [14,16,17].…”
mentioning
confidence: 99%
“…1). Hemispheric lesions are exceedingly rare, but up to 71 % may fulfill MRI diagnostic criteria for multiple sclerosis [16]. Progressive infratentorial atrophy, tumor-like lesions in the brainstem, and preservation of corpus callosum help in the differential diagnosis [5,15,16].…”
Section: Discussionmentioning
confidence: 99%